Instrumentation for Audiology and Hearing Science Theory and Practice. - Silman, Shlomo (Plural Publishing, Incorporated, 2019)
Understanding the array and complexity of instrumentation available to audiologists and hearing scientists is important to students, beginning clinicians, and even seasoned professionals. The second edition of Instrumentation for Audiology and Hearing Science: Theory and Practice is a comprehensive and accessible look at instrumentation used in these fields for research and clinical purposes. The expert authors introduce the laws of physics as they relate to audiology and hearing science and explain a range of concepts in electronics directly related to instrumentation used in audiology and he.